BRCA1 regulates glucose and lipid metabolism in diabetes mellitus with metabolic dysfunction-associated steatotic liver disease via the PI3K/Akt signaling pathway - Cui Ma; Xiaodi Yang; Liyin Zhang; Jie Zhang; Youyou Zhang; Xiaofeng Hu (PLoS ONE, 2025)
Purpose This study mimics the metabolic environment of metabolic dysfunction-associated steatotic liver disease (MASLD) and diabetic mellitus (DM) to investigate the function of BRCA1 in regulating glucose and lipid metabolism in hepatocytes under high glucose (HG) settings. Methods MASLD and DM-related datasets (GSE89632, GSE95849) were screened for overlapping genes, Protein-Protein Interaction (PPI) network and enrichment analyses were performed. Then, quantitative real-time polymerase chain reaction (qRT-PCR), Western Blotting (WB), and enzymatic colorimetric assays to examine the expression changes of BRCA1 in mouse primary hepatocytes under HG conditions and the impact of the combined PI3K/Akt signaling pathway on key metabolic markers of gluconeogenesis and lipid metabolism. Results Our study identified seven key overlapping genes (AURKA, BRCA1, ISG15, NUSAP1, OAS1, RSAD2, TLR7) between MASLD and DM. Experiments found that when BRCA1 was overexpressed in mouse primary hepatocytes, intracellular triglyceride content and lipid metabolism-related biomarkers (such as PEPCK, SREBP-1c, G6Pase, and FAS) were significantly increased in HG circumstances. However, the knockdown of BRCA1 reduced the expression of these indicators. Besides, we also observed that under HG conditions, the expression of proteins linked to the PI3K/Akt signaling pathway was negatively regulated by BRCA1 expression. Moreover, TG content and expression of lipid metabolism markers are also regulated by BRCA1 and PI3K/Akt pathway inhibitor Ly294002. Conclusion As a key regulator of hepatocyte metabolism under HG conditions, BRCA1 can participate in regulating glucose and lipid metabolism in mouse primary hepatocytes through the PI3K/AKT signaling pathway, which be able to become a possible remedy strategy for DM with MASLD.